Wedding tayo, wedding hindi - Gonzaga, Toni; Domingo, Eugene; Marudo, Zanjoe; Ramos, Wendell; Reyes, Jose Javier; Lucas, Jesse; Santos-Consio, Charo; Santos, Malou; Ilacad, Orly (Quezon City Star Cinema Productions, 2011)
Precy Matias (Eugene Domingo) a hard-working and diligent mother of two, is finally fed up with her husband, Ben's irresponsible handling of their finances. The money Precy had been saving was he ronly way to pay for a new house in Carmona to be able to get away from her condescending mother-in-law, Ursula Matias. But now tha tshe has reached her final straw, Precy declares tha tshe is leaving her husband. Despite Ben's protests, she walks out of the house with her belongings. A precy runs to her parent's comforting arms, they hear news of her favorite cousin, Belay's (Toni Gonzaga) return from Japan. After 3 years as a cultural worker there, Belay has now come back to fufull her engagement with her long-term boyfriend Oca, get married, and settle down in the Philippines.
VCD
Executive producers, Charo Santos-Concio, Malou Santos, Orly Ilacad ; writer and director, Jose Javier Reyes ; musical director, Jesse Lucas.
Toni Gonzaga, Eugene Domingo, Zanjoe Marudo, Wendell Ramos.
Keywords: Wedding tayo, wedding hindi (Motion picture).; Romantic comedy films; Feature films